Bibliometric Analysis of Mexican Publications on Stereotactic and Functional Neurosurgery From 1949 to 2021 - Carrillo-Ruiz, José Damián; Armas-Salazar, Armando; Navarro-Olvera, José Luis; Beltrán, Jesús Q.; Bowles, Brigham; González-Garibay, Guillermo; Lee, Ángel (Frontiers in Surgery, 2022)
Background: Stereotactic and Functional Neurosurgery (SFN) is a rapidly evolving field and some emerging countries, especially Mexico have made significant contributions to this discipline. A bibliometric analysis has never been performed in Latin America, and this would be particularly important to show the areas that remain poorly studied and design research strategies for the future. Methods: Scopus was queried using keywords pertaining to functional neurosurgery, restricting affiliation country to Mexico, and considering documents published after 1949. Added to the initial search, a complementary literature exploration by author considering the publications of the most productive neurosurgeons was performed. A descriptive statistical analysis was carried out. Results: From 5,109 articles only 371 were eligible. Scientific production has gradually increased with time. Epilepsy (31%) and movement disorders (27.4%) were the most studied neurological conditions, whereas the other 41.6% corresponded to pain, behaviour disorders, spinal cord injuries, neuromodulation, stereotactic biopsies, and SFN history. Level of evidence was predominantly level V (59.1%). Publication output is highly skewed to Mexico City representing 78.4% of national production. Relative to factors associated with impact of research, publications in English had more citations (28.5 mean citations per paper), and journals with an impact factor greater than one had more than 10 mean citations per paper. Conclusions: Mexico has experienced an increase in the productivity of SFN literature, addressing the most prevalent issues in the country (epilepsy and motor disorders). However, it is necessary to report studies with a higher level of evidence, as well as to decentralize the research collaborating with national institutions outside Mexico City. On the other hand, it is imperative to promote scientific production in English and in high-impact indexed journals to increase the visibility of our production. We would like to call upon our colleagues in other countries to reproduce our methodology, in order to determine the factors associated with the impact and productivity on SFN research.